ASSESSMENT OF THE RESULTS OF ESOPHAGOGASTROPLASTY OF SCARRY STRICTURE OF THE ESOPHAGUS AND ESOPHAGEAL ACHALASIA - Yu. V. Chikinev; E. A. Drobyazgin; I. E. Sudovykh; M. S. Anikina; E. K. Nurlanbaev (Вестник хирургии имени И.И. Грекова)
Department of hospital and pediatric surgery, Novosibirsk State Medical University OBJECTIVE. The authors made a complex assessment of functioning of the artificial esophagus, which was formed from the stomach. The pathological study of biopsy material of mucous coat of the stomach was carried out at different terms after surgery. MATERIALS AND METHODS. The research analyzed the results of esophagogastroplasty in cases of scarry strictures of the stomach after burns and esophageal achalasia in 101 patients. All the patients underwent extirpation of the esophagus with the gastric tube plasty. RESULTS. There weren’t noted any complications with gastric graft functioning. These data were confirmed by X-ray and endoscopy. The structural reorganization of the mucous coat with signs of atrophy was revealed according to the data of pathologic research. CONCLUSIONS. The authors indicated the necessity of the dynamic follow-up of the patients after esophagoplasty.